Design, synthesis and cholinesterase inhibitory properties of new oxazole benzylamine derivatives - Ivana Šagud; Nikolina Maček Hrvat; Ana Grgičević; Tena Čadež; Josipa Hodak; Milena Dragojević; Kornelija Lasić; Zrinka Kovarik; Irena Škorić (Taylor & Francis Group, 2020)
The enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are primary targets in attenuating the symptoms of neurodegenerative diseases. Their inhibition results in elevated concentrations of the neurotransmitter acetylcholine which supports communication among nerve cells. It was previously shown for trans-4/5-arylethenyloxazole compounds to have moderate AChE and BChE inhibitory properties. A preliminary docking study showed that elongating oxazole molecules and adding a new NH group could make them more prone to bind to the active site of both enzymes. Therefore, new trans-amino-4-/5-arylethenyl-oxazoles were designed and synthesised by the Buchwald-Hartwig amination of a previously synthesised trans-chloro-arylethenyloxazole derivative. Additionally, naphthoxazole benzylamine photoproducts were obtained by efficient photochemical electrocyclization reaction. Novel compounds were tested as inhibitors of both AChE and BChE. All of the compounds exhibited binding preference for BChE over AChE, especially for trans-amino-4-/5-arylethenyl-oxazole derivatives which inhibited BChE potently (IC50 in µM range) and AChE poorly (IC50≫100 µM). Therefore, due to the selectivity of all of the tested compounds for binding to BChE, these compounds could be applied for further development of cholinesterase selective inhibitors.HIGHLIGHTS Series of oxazole benzylamines were designed and synthesised The tested compounds showed binding selectivity for BChE Naphthoxazoles were more potent AChE inhibitors